Cryospheric ecosystems: a synthesis of snowpack and glacial research. (28th October 2015) - Hodson, Andy; Brock, Ben; Pearce, David; Laybourn-Parry, Johanna; Tranter, Martyn
Abstract: The fourteen letters that contributed to this focus issue on cryospheric ecosytems provide an excellent basis for considering the state of the science following a marked increase in research attention since the new millennium. Research letters from the focus issue provide significant insights into the biogeochemical and biological processes associated with snow, glacier ice and glacial sediments. This has been achieved via a significant, empirical effort that has given particular emphasis to glacier surface habitats. However, far less is known about aerobiology, glacial snow covers, supraglacial lakes and sub-ice sedimentary habitats, whose access for sampling and in-situ monitoring remains a great challenge to scientists. Furthermore, the use of models to explore key fluxes, processes and impacts of a changing glacial cryosphere are conspicuous by their absence. As a result, a range of process investigations and modelling studies are required to address the increasing urgency and uncertainty that is associated with understanding the response of cryospheric ecosystems to global change.